Faktor Determinan Analisis Niat Siswi Mengkonsumsi Tablet Tambah Darah Di SMP Negeri 14 Bandar Lampung - Dewi Sri Sumardilah; Bertalina Bertalina; Nawasari Indah Putri Sejati (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2026)
Iron deficiency anemia remains a nutritional problem among adolescent girls, due to low iron intake from daily food and monthly blood loss due to menstruation. To prevent anemia, the Indonesian government has implemented an iron supplementation program through weekly iron supplementation tablets (TTD) for female students since 2014. However, compliance with iron supplementation remains low due to low intention, thus suboptimal program effectiveness. Intention to consume iron supplementation is influenced by adolescents' attitudes, subjective norms, and behavioral control. This study aims to determine the relationship between attitudes, subjective norms, and behavioral control with iron supplementation intention in adolescent girls. This study used a cross-sectional approach at SMP Negeri 14 Bandar Lampung. Respondents were 224 female students in grades VII, VIII, and IX, with a sample size determined using the Slovin formula and drawn using stratified random sampling. The dependent variable was intention to consume iron supplementation, while the independent variables were attitude, subjective norms, and behavioral control. Data were analyzed using the chi-square test. The results showed that 51.3% of female students had a strong intention to drink iron tablets. There was a significant relationship between attitude (p = 0.000; OR = 3.1), subjective norm (p = 0.015; OR = 2.2) and students' intention to drink iron tablets. Furthermore, there was no significant relationship between behavioral control (p = 0.077) and students' intention to drink iron tablets. It is recommended that schools, through teachers and school health workers, facilitate the provision of iron tablets in sufficient quantities and increase supervision during joint iron tablet drinking activities at school.